Russian Society for the Prevention of Noncommunicable Diseases (ROPNIZ). Alimentary-dependent risk factors for chronic non-communicable diseases and eating habits: dietary correction within the framework of preventive counseling. Methodological Guidelines - O. M. Drapkina; N. S. Karamnova; A. V. Kontsevaya; B. E. Gorny; V. A. Dadaeva; L. Yu. Drozdova; R. A. Yeganyan; S. O. Eliashevich; O. V. Izmailova; E. A. Lavrenova; O. V. Lischenko; I. A. Skripnikova; et al. (Кардиоваскулярная терапия и профилактика, 2021)
The methodological guidelines are developed as a practical document for medical specialists working in the field of preventive medicine, in order to expand and improve the provision of this type of medical service to the adult population. The methodological guidelines include an informational and informative part for medical specialists and a practical part for patients, presented in the format of memos, contain the main sections-healthy nutrition, correction of eating habits, issues of modifying the diet for the main alimentary-dependent risk factors for chronic non-communicable diseases, such as arterial hypertension, obesity, disorders of lipid, carbohydrate and purine metabolism, a decrease in bone mineral density. They are intended for medical specialists working in the field of prevention, for doctors and secondary medical personnel of offices and departments of medical prevention, public health and medical prevention centers, healthy lifestyle specialists, teachers of medical educational institutions, for specialists who develop and implement educational programs for patients, as well as for medical specialists of a therapeutic profile.